Non-native Nematode Ashworthius sidemi Currently Dominates the Abomasal Parasite Community of Cervid Hosts in the Czech Republic - Magdálek, Jan; Bourgoin, Gilles; Vadlejch, Jaroslav (Frontiers in Veterinary Science, 2022)
Ashworthius sidemi is an abomasal nematode typical for Asiatic cervids such as sambar (Rusa unicolor) or sika deer (Cervus nippon). This non-native parasite was introduced into Europe via sika deer in the late 19th and early 20th centuries. The current dynamic spread of this parasite amongst autochthonous wild cervids occurs independently of human activities, and A. sidemi has a negative impact on the health of wild ruminants and may pose a threat to the conservation of endangered wild ungulates and to livestock. This invasive parasite has been previously detected in the Czech Republic, but more accurate information on A. sidemi is required. Only limited information is generally available on the factors influencing the spread of abomasal nematodes in wild ruminants, so more information is necessary for planning effective strategies of parasite control. We therefore conducted a survey on the abomasal nematodes in cervids in both game reserves and hunting grounds across the Czech Republic, taking into account the hosts (species, age, sex) and environmental factors (monthly average temperature). The abomasa of 104 animals belonging to five cervid species originating from various locations of the country were collected. Data on host (species, sex, and age group) and the monthly average temperature in the region were obtained for each animal. The parasitological analyses indicated that 92% of the abomasa were infected by nematodes. Ashworthius sidemi was the most prevalent (72%) and abundant (80% of the total recovered individuals) nematode species and was detected in all cervid species except white-tailed deer. The intensity of A. sidemi was highest in roe deer (Capreolus capreolus) and fallow deer (Dama dama), but A. sidemi abundance did not depend substantially on the host or environmental factors. In contrast, the abundance of nematodes from the subfamily Ostertagiinae was influenced by the host species and temperature. Parasitic load was significantly higher in roe deer and during the warmer periods of the survey. We also detected another non-native nematode species, Spiculopteragia houdemeri. The results of our study suggest that the non-native nematode A. sidemi is now widespread amongst cervid hosts in the Czech Republic, probably due to the high sensitivity of autochthonous cervids to A. sidemi infections as well as adaptation of this parasite to the current climatic conditions of this country.